Rancang Bangun Media Pembelajaran Pengenalan Spesies Ikan dengan Teknologi Augmented Reality - Martono, Kurniawan Teguh; Fauzi, Adnan (Jurusan Teknik Elektro Universitas Negeri Semarang, 2018)
Education is one process that has a goal to develop the potential that exists in itself optimally. The education process can not be separated from the role of educators, infrastructure and society. In this era, the biggest challenge in the world of education is how to develop learning media that have interactive properties. The development of computer technology brought changes in the process of interaction between students and teachers. The computer technology used in this research is by using Augmented Reality technology. To know the working function of existing components in this application is done testing process with blackbox testing. This test is done by testing the effect of camera angle on marker and the influence of light in detecting marker. Based on the results of blackbox testing that has been done then obtained the bottom results in the conditions of light intensity 5 - 9 lux with angle orintation from 10 to 90 degrees marker failed to detect this is because the light intensity in the room does not meet so that the camera difficulty in performing marker detection. Markers can be detected when the light intensity is increased from 20 to 200 lux with an angle greater than or equal to 30o.